Influence of substitutional disorder on the electrical transport and the superconducting properties of Fe1+zTe1-x-ySexSy - Rodríguez, M. G. (2015)
We have carried out an investigation of the structural, magnetic, transport and superconducting properties of Fe1+zTe1-x-ySexSy ceramic compounds, for z = 0 and some specific Se (0 ≤ x ≤ 0.5) and S (0 ≤ y ≤ 0.12) contents. The incorporation of Se and S to the FeTe structure produces a progressive reduction of the crystallographic parameters as well as different degrees of structural disorder associated with the differences of the ionic radius of the substituting cations. In the present study, we measure transport properties of this family of compounds and we show the direct influence of disorder in the normal and superconductor states. We notice that the structural disorder correlates with a variable range hopping conducting regime observed at temperatures T > 200 K. At lower temperatures, all the samples except the one with the highest degree of disorder show a crossover to a metallic-like regime, probably related to the transport of resilient-quasi-particles associated with the proximity of a Fermi liquid state at temperatures below the superconducting transition. Moreover, the superconducting properties are depressed only for that particular sample, in accordance to the condition that superconductivity is affected by disorder when the electronic localization length ξL becomes smaller than the coherence length ξSC.